1990
DOI: 10.1007/bf00636168
|View full text |Cite
|
Sign up to set email alerts
|

Reaming versus non-reaming in medullary nailing: Interference with cortical circulation of the canine tibia

Abstract: Medullary nails have only been used with reluctance in the treatment of open fractures since reaming interferes with the cortical circulation. The technique of interlocking offers the interesting possibility of inserting a relatively stiff nail which does not necessarily require reaming. The effects of reaming prior to nail insertion upon the cortical circulation was investigated in the canine tibia. Intravital staining with procion red was used to trace areas of disturbed circulation. Nail insertion without r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
95
1
9

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(106 citation statements)
references
References 8 publications
1
95
1
9
Order By: Relevance
“…In the lateral view, a minor correction into flexion with slight anterior translation was achieved as planned recommendation is preservation of the endosteum by cortical osteotomies [83]. Some authors hypothesise that reaming may compromise endosteal blood supply and, thus, affect the quality of the regenerate [135,136]. However, there is evidence that the periosteal blood supply may increase after intramedullary nailing, which is particularly important for effective distraction osteogenesis [76,137].…”
Section: Intramedullary Fixation: General Considerationsmentioning
confidence: 99%
“…In the lateral view, a minor correction into flexion with slight anterior translation was achieved as planned recommendation is preservation of the endosteum by cortical osteotomies [83]. Some authors hypothesise that reaming may compromise endosteal blood supply and, thus, affect the quality of the regenerate [135,136]. However, there is evidence that the periosteal blood supply may increase after intramedullary nailing, which is particularly important for effective distraction osteogenesis [76,137].…”
Section: Intramedullary Fixation: General Considerationsmentioning
confidence: 99%
“…Non-union was significantly high in the unreamed rather than reamed group in this study but some studies shows that reamed intramedullary nailing might destroy the nutrient artery, which is the main source of blood for 70% of the tibial cortex would impair fracture healing and increase infection [8,9]. Reamed intramedullary nailing results in increased contact area between the implant and the bone surface and thus increases stability, permitting early weight bearing and eventually facilitating fracture union [10,11].…”
Section: Discussionmentioning
confidence: 70%
“…This procedure secured axial alignment, maintained length gained, and prevented refracture after external fixator removal. Some authors have expressed concern that intramedullary nailing may compromise the endosteal blood supply of diaphyseal bone and thus affect the quality of newly formed bone during leg-lengthening procedures [8,15,18]. However, it has been shown that the periosteum and surrounding soft tissue can support osteogenesis and permit new bone formation, and it is also known these issues are particularly important for effective distraction osteogenesis [9,19,20].…”
Section: Discussionmentioning
confidence: 99%